2011
DOI: 10.5301/jva.2011.8413
|View full text |Cite
|
Sign up to set email alerts
|

Vascular Access Cannulation in Hemodialysis Patients – A Survey of Current Practice and its Relation to Dialysis dose

Abstract: This survey covered a broad number of countries and centers and provides information on current practice of vascular access cannulation, their effect on dialysis dose, and serves as feedback to the dialysis centers for their quality management process.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
21
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(23 citation statements)
references
References 12 publications
2
21
0
Order By: Relevance
“…Studies in which the distance between puncture needles was analyzed do not describe how distance was measured. 17,21 In our study, the vascular access with the shortest distance between the needles was AVF (93%), proximal (55%), and with anterograde cannulation (98%). These characteristics suggest that fistulas probably had smaller extension for cannulation.…”
Section: Tablementioning
confidence: 60%
See 2 more Smart Citations
“…Studies in which the distance between puncture needles was analyzed do not describe how distance was measured. 17,21 In our study, the vascular access with the shortest distance between the needles was AVF (93%), proximal (55%), and with anterograde cannulation (98%). These characteristics suggest that fistulas probably had smaller extension for cannulation.…”
Section: Tablementioning
confidence: 60%
“…Several results of our study are in agreement with those reported by others. Gauly et al 17 , in 2011, published an extensive multicenter study involving 10,807 patients from 171 Fresenius Medical Care clinics, in nine European countries and South Africa. Table 7 shows the main features of cannulation techniques observed in that study compared to our results.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Conversely, the findings of this study disagree with the conclusion made by previous studies stating that there was no significant difference in dialysis adequacy parameters between antegrade and retrograde arterial needle placement [11,[13][14][15][16]18]. Furthermore, the findings of this study are incongruent with the conclusions drawn from previous study that revealed that the retrograde placement of the arterial needle had a significantly higher probability to attain Kt/V of 1.20 and that retrograde with a needle distance of 10 cm or more presented the best Kt/V values [12,19]. In addition, English reported a small advantage to retrograde insertion showed that the retrograde direction of placement of the arterial needle was proposed to improve dialysis adequacy and recommended to be used more frequently in the dialysis setting [20].…”
Section: Discussionmentioning
confidence: 53%
“…On the other hand, Molaei et al revealed that the recirculation rate had a significant relationship with the direction of needle placement and the space between two arteriovenous fistula needles [31]. As supported by the claim of Gauly et al that enlarging the distance between bevels of the arterial and venous needles decreases access recirculation [19].…”
Section: Discussionmentioning
confidence: 99%